2016
DOI: 10.1111/bdi.12367
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype is not associated with cognitive impairment in older adults with bipolar disorder

Abstract: APOE*4 is not associated with the diagnosis of BD and does not impact the occurrence of dementia in BD. Given the distinct clinical and biological features of cognitive impairment in BD, we hypothesized that dementia in BD is unrelated to AD pathological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Two recent studies conducted in our group demonstrated that older, cognitively impaired, BD patients do not display a significant effect of the apolipoprotein E*4 allele,61 or the pathological markers of AD in the cerebrospinal fluid62 – the so-called “pathological signature” of AD in the cerebrospinal fluid, which is defined by reduced concentrations of the Aβ peptide along with increased total Tau and phosphorylated Tau 62,63. These findings suggest that the dementing process in BD follows a distinct biological route compared to AD, which is compatible with the distinct pattern observed in clinical progression of neuropsychological deficits.…”
Section: Neurobiological Correlates Of Geriatric Depression and Bd Gementioning
confidence: 60%
“…Two recent studies conducted in our group demonstrated that older, cognitively impaired, BD patients do not display a significant effect of the apolipoprotein E*4 allele,61 or the pathological markers of AD in the cerebrospinal fluid62 – the so-called “pathological signature” of AD in the cerebrospinal fluid, which is defined by reduced concentrations of the Aβ peptide along with increased total Tau and phosphorylated Tau 62,63. These findings suggest that the dementing process in BD follows a distinct biological route compared to AD, which is compatible with the distinct pattern observed in clinical progression of neuropsychological deficits.…”
Section: Neurobiological Correlates Of Geriatric Depression and Bd Gementioning
confidence: 60%
“…We found 53 articles on OABD in the last 6 years . Of those, 50 (94%) papers examined clinical samples ranging from 10 to 315 subjects (total of 3302 subjects, mean ± standard deviation (SD) 62.3 ± 51.5 subjects/paper, median 53 subjects/paper).…”
Section: Resultsmentioning
confidence: 99%
“…All studies ( n = 53) reported age and gender. Levels of education were the next most often reported ( n = 34 studies, 64%), followed by ethnicity ( n = 23, 43%) and marital status ( n = 17, 32%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations